Analisis Pengaruh Harga, Promosi, Lokasi dan Kualitas Pelayanan terhadap Loyalitas Konsumen (Studi pada Alfamart Jl. Magelang Km.16 Yogyakarta) - Ratnaningtyas, Endah Marendah; Narisistiwi, Meila; Harti, Farida Puspita; Lestari, Suin; Puspitaningnala, Diva Rifdah Rizkia (JURNAL ECONOMINA, 2024)
The development of retail in Indonesia is experiencing significant growth. Since then the competition in the retail business has changed in total foreign investors began to enter big cities in Indonesia to invest. However, along with the tight competition between retail companies, it requires entrepreneurs to innovate their services. Against the background of these problems, then this research was carried out to determine the effect of price, promotion, location and service qualityon consumer loyalty. The approach used in this study is a quantitative approach. Data collection instruments using questionnaires. The data analysis technique in this study uses multiple regression analysis t test and F test with the program used is SPSS version 25. Thedetermination of sempel results using a likert scale, obtained as many as 104 respondents and taken by area (cluser) sampling (sampling by region). The results showed that price and service quality simultaneously had a significant effect on consumer loyalty, while promotion and location had an insignificant effect on consumer loyalty. Price is the most influential variable on consumer loyalty of Alfamart Jalan Magelang Km.16. The influence of price, promotion, location and service quality variables on consumer loyalty variables is 58,7%.